PRaVDA: The first solid-state system for proton computed tomography. (November 2018) - Esposito, Michela; Waltham, Chris; Taylor, Jonathan T.; Manger, Sam; Phoenix, Ben; Price, Tony; Poludniowski, Gavin; Green, Stuart; Evans, Philip M.; Allport, Philip P.; Manolopulos, Spyros; Nieto-Camero, Jaime; et al.
Highlights: A novel proton CT imaging system, based entirely on solid-state detector technology. First proton CT scan with solid-state detectors. Potential for short scan times as well as improvement in RSP accuracy. Abstract: Purpose: Proton CT is widely recognised as a beneficial alternative to conventional X-ray CT for treatment planning in proton beam radiotherapy. A novel proton CT imaging system, based entirely on solid-state detector technology, is presented. Compared to conventional scintillator-based calorimeters, positional sensitive detectors allow for multiple protons to be tracked per read out cycle, leading to a potential reduction in proton CT scan time. Design and characterisation of its components are discussed. An early proton CT image obtained with a fully solid-state imaging system is shown and accuracy (as defined in Section IV) in Relative Stopping Power to water (RSP) quantified. Method: A solid-state imaging system for proton CT, based on silicon strip detectors, has been developed by the PRaVDA collaboration. The system comprises a tracking system that infers individual proton trajectories through an imaging phantom, and a Range Telescope (RT) which records the corresponding residual energy (range) for each proton. A back-projection-then-filtering algorithm is used for CT reconstruction of an experimentally acquired proton CT scan. Results: An initial experimental result for proton CT imaging with a fully solid-state system is shown for an imaging phantom, namely a 75 mm diameter PMMA sphere containing tissue substitute inserts, imaged with a passively-scattered 125 MeV beam. Accuracy in RSP is measured to be ⩽ 1.6% for all the inserts shown. Conclusions: A fully solid-state imaging system for proton CT has been shown capable of imaging a phantom with protons and successfully improving RSP accuracy. These promising results, together with system the capability to cope with high proton fluences ( 2 × 10 8 protons/s), suggests that this research platform could improve current standards in treatment planning for proton beam radiotherapy.